Structure-Properties Relationship Of Open Cell Ethylene Vinyl Acetate Foam For Sound Insulation Application - Atan, Mohd Nidzam Adha (Universiti Sains Malaysia, 2022)
The effect of structure-properties relationship of open cell ethylene vinyl acetate (EVA) foam for sound insulation applications has been studied. This project aimed to prepare open-cell EVA foam by manipulating the blowing agent, azodicarbonamide (ADC) used for each sample. There were five different formulations used in order to obtain different types of open cell EVA foam. To produce the foam, mastication and compounding process was done to obtain a compound of mixture the foam ingredients. Next, foaming process was done by two-step of heating process. The foaming process was done twice to obtain two sets of samples consists of all five of different ADC loadings with different processing strategies. The difference for each set was during the second step of heating process. The first step of heating was done at lower temperature than the second step which was 140°C for 30 minutes, while for the second stage of heating the temperature was at 180°C for 6 minutes 50 second for Sample 1 and 6 minutes 30 second for Sample 2. The samples were then characterized by undergoes a few testings including sound absorption coefficient test and transmission loss test to evaluate the foam acoustic properties. After the characterization was done it was found that the main influence on open cell EVA foam acoustic performance was by the foaming time during the second stage of heating process. The longer the foaming time, the better the acoustic properties the foam had. Thus, sample 1 had better properties for sound insulation application compared to sample 2.